Development and content validity of the Experienced Patient‐Centeredness Questionnaire (EPAT)-A best practice example for generating patient‐reported measures from qualitative data - Eva Christalle; Stefan Zeh; Pola Hahlweg; Levente Kriston; Martin Härter; Jördis Zill; Isabelle Scholl (Wiley, 2022)
Abstract Introduction To effectively foster patient‐centeredness (PC), it is crucial to measure its implementation. So far, there is no German measure to assess PC comprehensively. The aim of this study is to develop and select items for the Experienced Patient‐Centeredness (EPAT) Questionnaire, a patient‐reported experience measure (PREM). The EPAT intends to assess PC from the perspective of adult patients treated for different chronic diseases in inpatient and outpatient settings in Germany. Furthermore, we aim at providing a best‐practice example for developing PREMs from qualitative data. Methods The development process comprised a three‐phase mixed‐method design: (1) preparation, (2) item generation and (3) item selection and testing of content validity. We generated items using qualitative content analysis based on information from focus groups, key informant interviews and literature search. We selected items using relevance rating and cognitive interviews. Participants were patients from four chronic disease groups (cancer, cardiovascular disease, mental disorder, musculoskeletal disorder) and healthcare experts (e.g., clinicians, researchers, patient representatives). Results We conducted six focus groups with a total of 40 patients, key informant interviews with 10 experts and identified 48 PREMs from international literature. After team discussion, we reached a preliminary pool of 152 items. We conducted a relevance rating with 32 experts and 34 cognitive interviews with 21 patients. We selected 125 items assessing 16 dimensions of PC and showed high relevance and comprehensibility. Conclusions The EPAT questionnaire is currently undergoing psychometric testing. The transparent step‐by‐step report provides a best practice example that other researchers may consider for developing PREMs. Integrating literature and experts with a strong focus on patient feedback ensured good content validity. The EPAT questionnaire will be helpful in assessing PC in routine clinical practice in inpatient and outpatient settings for research and quality improvement. Patient or Public Contribution Patients were not involved as active members of the research team. While developing the funding proposal, we informally reached out to several patient organizations who all gave us positive feedback on the study aims, thereby confirming their relevance. Those patient organizations endorsed the funding proposal with formal letters of support and supported recruitment by disseminating advertisements for study participation.